Memaknai Penerapan Sistem Pengendalian Manajemen Pada Perusahaan Keluarga Etnis Tionghoa Di Minangkabau - Tabah Rizki; Sany Dwita (Universitas Negeri Padang, 2019)
This study aims to interpret in depth the cultural values ​​of Confucianism reflected in the management control system of Chinese ethnic families in Minangkabau. This study uses qualitative interpretive. The process of this research is interactive and meaning that is not measured by statistical data and aims to explore various information more in depth and makes it possible to get things implied by data collection carried out in triangulation. Data analysis is inductive and the results of qualitative research emphasize the meaning of generalization. This interpretive research method seeks to formulate a question and then analyze it based on the question of participants' perceptions studied. This research was conducted in one of the food trading businesses in the city of Padang, namely UD. KBF. The results of the study can be concluded by interpreting Confucian cultural values ​​in the implementation of the management system of Chinese ethnic family companies. This study found that Confucian values ​​were reflected in the implementation of the company's management control system UD. KBF. The values ​​applied by the company's leadership are